2016
DOI: 10.17549/gbfr.2016.21.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Authentic Leadership and its Consequences in a Hotel Restaurant Context

Abstract: A B S T R A C TThis paper examines the effect of authentic leadership on leader trust, organizational identification, job performance, and employee loyalty within the context of a food-and beverage department in a hotel. The data were collected from 204 hotel employees and analyzed using structural equation modeling. Findings are as follows: authentic leadership had significant effects on leader trust and job performance, but does not affect organizational identification. Leader trust was found to have signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 76 publications
(100 reference statements)
0
10
0
Order By: Relevance
“…Particularly, O'Reilly and Chatman (1986) argued that members who are attached to an organization through organizational identification are more likely to engage in prosocial behavior than are members who are attached to an organization through prudential motives. Lee et al(2016) insisted that organizational identification has a positive effect on job performance. Bell and Menguc (2002) also pointed out that organizational identification has a significantly positive effect on all five sub-factors of organizational citizenship behavior.…”
Section: B Organizational Identification As a Determinant Of Turnovementioning
confidence: 99%
“…Particularly, O'Reilly and Chatman (1986) argued that members who are attached to an organization through organizational identification are more likely to engage in prosocial behavior than are members who are attached to an organization through prudential motives. Lee et al(2016) insisted that organizational identification has a positive effect on job performance. Bell and Menguc (2002) also pointed out that organizational identification has a significantly positive effect on all five sub-factors of organizational citizenship behavior.…”
Section: B Organizational Identification As a Determinant Of Turnovementioning
confidence: 99%
“…The issue that the formation of positive trust is a major leading variable of loyalty has been discussed in many studies (Delgado-Ballester and Aleman, 2001;Lau and Lee, 1999;Lee, Lim, Swanson, Park, & Lee, 2016). In the study by Morgan and Hunt (1994), it was found that trust and commitment are major factors in deriving successful relationships between sellers and buyers (consumers) and that commitment, which is a concept similar to loyalty, is, in fact, a leading variable of loyalty.…”
Section: Relationship Between Trust and Loyalty (Wom)mentioning
confidence: 99%
“…The theory of social ex change is trust-based relationships that the people involved in exchange will be mutually beneficial. Furthermore, it is used to confirm the relationship between supe rior's leadership and follower's trust beyond economic and transactional ex change between them (Lee et al, 2016). Leaders with positive psychological capa bilities (i.e.…”
Section: Hypothesis Development Authentic Leadership and Trustmentioning
confidence: 99%
“…Accor dingly, employees can carry out their duties faithfully through the leader's authentic leadership. This leads to employee's identi fication within the organization based on their trust in leaders, which is ultimately improving job performance (Lee et al, 2016).…”
Section: Introductionmentioning
confidence: 99%